2022
DOI: 10.1038/s42003-022-03417-6
|View full text |Cite
|
Sign up to set email alerts
|

Cargo receptor Surf4 regulates endoplasmic reticulum export of proinsulin in pancreatic β-cells

Abstract: Insulin is an essential peptide hormone that maintains blood glucose levels. Although the mechanisms underlying insulin exocytosis have been investigated, the mechanism of proinsulin export from the endoplasmic reticulum (ER) remains unclear. Here, we demonstrated that Surf4, a cargo receptor homolog, regulates the ER export of proinsulin via its recruitment to ER exit sites (ERES). Under high-glucose conditions, Surf4 expression was upregulated, and Surf4 proteins mainly localized to the ER at a steady state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…elegans lipoproteins that share about 22% sequence identity with human apolipoprotein B (APOB); this same group demonstrated that SURF4 also serves as a cargo receptor for APOB in human hepatic HepG2 cells ( 162 ). Several other SURF4 cargoes have been identified, including growth hormone, dentin sialophosphoprotein (DSPP), amelogenin ( 163 ), erythropoietin ( 164 ), pathogenic A1AT polymers ( 165 ), sonic hedgehog ( 166 ), proinsulin ( 167 ), and the lysosomal proteins progranulin and prosaposin ( 168 ).…”
Section: Specificity Of Cargo Receptorsmentioning
confidence: 99%
“…elegans lipoproteins that share about 22% sequence identity with human apolipoprotein B (APOB); this same group demonstrated that SURF4 also serves as a cargo receptor for APOB in human hepatic HepG2 cells ( 162 ). Several other SURF4 cargoes have been identified, including growth hormone, dentin sialophosphoprotein (DSPP), amelogenin ( 163 ), erythropoietin ( 164 ), pathogenic A1AT polymers ( 165 ), sonic hedgehog ( 166 ), proinsulin ( 167 ), and the lysosomal proteins progranulin and prosaposin ( 168 ).…”
Section: Specificity Of Cargo Receptorsmentioning
confidence: 99%
“…Surf4 has been implicated in ER export of diverse cargos, such as EPO, α1AT, and proinsulin ( Lin et al., 2020 ; Ordonez et al., 2021 ; Saegusa et al., 2022 ). EPO is mainly secreted into the blood by interstitial cells in the peritubular capillary bed of the renal cortex.…”
Section: Surf4 a Highly Conserved Cargo Receptormentioning
confidence: 99%
“…(2021) reported that Surf4 mediated ER–Golgi transport of both α1AT monomer and polymer in CHO cells, with a preference for the polymer. In addition, Saegusa et al. (2022) reported that Surf4 directly interacted with proinsulin and mediated the transport of proinsulin from the ER to the Golgi apparatus in cultured rat pancreatic beta cells.…”
Section: Surf4 a Highly Conserved Cargo Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, ERES size and number have been shown to increase with elevated secretory load (Farhan et al, 2008a). Specialized cell types with high biosynthetic and secretory capacities can display dozens to hundreds of ERESs, while simpler cells can display as few as a single ERES (Saegusa et al, 2022; Stephens, 2003; Warren, 2013; Yelinek et al, 2009). In Drosophila neurons, genes involved in ERES function have been shown to play an important role in dendritic arbor development (Ye et al, 2007).…”
Section: Introductionmentioning
confidence: 99%